Research on intelligent control technology for OSU-based OTN - Yanxia TAN; Zhiyan DUAN; Xiangkun MAN; He ZHANG; Yacheng LIU; Yantao ZHOU; Shan DONG (Dianxin kexue)
With the development of information and cloud technology, the dynamic demand for OTN service is gradually increasing.As a next generation OTN switching technology, OSU needs to provide network and cloud services for high-quality enterprise leased lines and boutique home broadband services.The OSU-based OTN needs to be able to provide integrated services and automated service provisioning through end-to-end management and control capabilities to support one-hop service into the cloud.Firstly, the background, technical characteristics, and standardization progress of OSU technology were introduced.Then, a service-aware control framework for OSU-OTN was proposed to meet the demand for efficient bearer of government and enterprise leased lines.Finally, an experimental validation of the end-to-end management and control capability of the access OSU-OTN controller system was carried out.